Interaction between intestinal flora and gastric cancer in tumor microenvironment - Yang, Mingjin (Frontiers in Oncology, 2024)
Gastric Cancer (GC) is a prevalent malignancy globally and is the third leading cause of cancerrelated deaths. Recent researches focused on the correlation between intestinal flora and GC. Studies indicate that bacteria can influence the development of gastrointestinal tumors by releasing bacterial extracellular vesicles (BEVs). The Tumor microenvironment (TME) plays an important role in tumor survival, with the interaction between intestinal flora, BEVs, and TME directly impacting tumor progression. Moreover, recent studies have demonstrated that intestinal microflora and BEVs can modify TME to enhance the effectiveness of antitumor drugs. This review article provides an overview and comparison of the biological targets through which the intestinal microbiome regulates TME, laying the groundwork for potential applications in tumor diagnosis, treatment, and prognosis.